Persepsi Pemuda Desa terhadap Pekerjaan di Sektor Pertanian (Studi Kasus di Desa Bajang, Kecamatan Pakong, Kabupaten Pamekasan) - Zuhriyah, Amanatuz; Mabruhatin, Aini (AGRIMOR, 2024)
Bajang Village is a rural area where the majority of the translation are farmers. But, farmers in Bajang Village are dominated by farmers who in old age. This resulted in a lack of youth contribution to agriculture. This purpose of study are (1) to know the perception of Bajang Village youth about agricultural work (2) to know what factors have a relationship with the perception of Bajang Village youth regarding work in the agricultural sector. In this study, 40 respondents were used who were taken by accidental sampling. Data collection was carried out through observation, interviews, and dissemination of questionnaires. The data were analyzed using descriptive statistics and the Chi-square test. The results of the study showed that the perception of rural youth towards work in agriculture was in the good category. Factors related to youth's perception of employment in the agricultural sector include current employment, work experience and parental income. Meanwhile, the factors that have nothing to do with the perception of rural youth towards employment in the agricultural sector are gender, age, education and socialization.